The State of Law : Comparative Perspectives on the Rule of Law in Germany and Vietnam - Alemann, Ulrich von; Baurmann, Michael; Briesen, Detlef; Briesen, Detlef; Cong Giao, Vu; Duc Anh, Pham; Duy Anh, Phan; Haucap, Justus; Khanh, Lai Quoc; Khanh, Lai Quoc; Krüper, Julian; Mengyue, Liu; et al. (düsseldorf university press, 2017)
This book is the result of the first interdisciplinary conference in Vietnam which took place on "the Rule of Law." Instead of beginning immediately with a highly specialized debate from the perspective of one single academic discipline, we started to discuss numerous facets of the subject arising from a multidisciplinary dialogue. For this reason, the contributions for this publication come from various scientific disciplines in Vietnam and Germany: political, historical, social, economic and legal sciences, but also members of Vietnamese governmental and non-governmental organizations. The aim of the volume is to open up a dialogue about the Rule of Law between two very different legal cultures, the German-European and the Vietnamese-Southeast Asian.